American furies: crime, punishment, and vengeance in the age of mass imprisonment - Abramsky, Sasha (Beacon Press, 2007)
Introduction: From out of Tartarus -- The holy experiment -- A rising tide of violence -- Using a sledgehammer to kill a gnat -- Victims, fundamentalists, and rant radio hacks -- Reducto ad absurdum -- Open for business -- Till the end of time -- Storehouses of the living dead -- Adult time -- Conclusion: Leviathan calling